Rehab Emergencies for PGY-2 PM & R Residents: Autonomic Dysreflexia (AD) - Benjamin Seidel; Michael Mallow; Katherine Berg; Dale Berg (Association of American Medical Colleges, 2015)
Abstract Introduction This rehabilitation-related emergency situation in a spinal cord-injured patient is part of a pilot program for medical residents beginning their rehabilitation residency. The program was designed to expose rehabilitation residents to potential emergencies that might be encountered in the clinical setting of a rehabilitation facility, particularly when on call. By using a simulated patient, we can mimic the emergency situation without the stress of dealing with an actual emergency, thus allowing residents to practice in a safe environment. Methods In terms of the overall time frame, we had residents arrive at 7:30 a.m. for prebriefing and setup. The exercise started at 8:00 a.m. and took exactly 2 hours to execute, being that each encounter lasted 15 minutes total. At 10:00 a.m., everyone (staff, standardized patients, residents) met for the debriefing, which lasted about 45 minutes. After a short break, a didactic presentation was given to residents (11:00-11:30 a.m.), including time for questions. Thirty additional minutes were provided for cleanup, and everything ended at noon. Results Overall, this exercise ran smoothly, and all residents thought it was a good use of their time. In their assessments of the activity in a postquiz, as well as during the debriefing, residents were positive, and all indicated they would participate in this type of activity again. With the promise of expansion, residents felt this would be a strong adjunct to their orientation into a physical medicine and rehabilitation residency. Discussion Although the encounter was designed for rehabilitation residents, it could be applied to any number of medical professionals who encounter patients outside the rehabilitation setting. With minimal modifications, this resource could be applied for use in a family practice setting, emergency department, or skilled nursing facility. As such, family practice residents, emergency medicine residents, physician' assistants, and nurse practitioners could conceivably participate in this exercise.